A nonlinear perturbation study of a shoreface nourishment on a multiply barred beach. (1st February 2021) - Chen, W.L.; Dodd, N.
Abstract: The 1D (cross-shore) nonlinear nourishment-as-a-perturbation model of Chen and Dodd (2019) is extended to include wave streaming and depth-varying mean return flow. This is shown to lead to physically consistent values for the migration rate of small amplitude bed perturbations in the whole nearshore region. The model is also extended to arbitrary wave incidence angle, and an alternative energy dissipation description is included. The model is applied to a background profile that includes multiple nearshore bars, and which also allows comparison with observations of nourishment development and migration. The chosen profile is that of the Terschelling shoreface nourishment. Over the initial nourishment region the linearised bed evolution equation predicts onshore small-amplitude bed perturbation migration rates in the troughs (where waves shoal) and offshore rates on the bars (where waves break). Sensitivity studies using the fully nonlinear model reveal wave height to be the primary controlling parameter for the resultant perturbed sediment flux. Perturbed sediment fluxes are onshore up to a threshold wave height; beyond this offshore fluxes predominate. Wave period and angle of incidence, and tide level are all secondary controlling factors, variation in which yields no change in perturbed sediment flux sign (for fixed wave height). Recorded wave and tide signals are used to drive the model to simulate six months of the initial nourishment evolution. It is shown that in calmer conditions the small amplitude migration rate of bed disturbances is a highly accurate predictor of the fully nonlinear migration rate (as described by the centre of mass of the nourishment); in storm periods the two predictors diverge. The observed overall migration rate is well described by the model. The details of the profile evolution show a moderately good reproduction of those observed (Brier Skill Score = 0.52 ). Highlights: A nonlinear nourishment-as-a-perturbation model is developed and applied to study a shoreface nourishment on a barred beach. The Terschelling nourishment morphodynamics over the initial six months are simulated with recorded wave and tide signals. Sensitivity studies reveal wave height to be the primary controlling parameter for the resultant perturbed sediment flux. The propagation speed of bed perturbation is an accurate predictor of the nonlinear migration rate in calmer conditions. The observed overall migration rate and evolution of the nourishment is well described by the model.